Elaboración de una biopelícula a partir de pectina extraída de los residuos del maracuyá (2023)
This degree work shows the experimental development of a biofilm based on the use of pectins extracted from passion fruit waste as a design basis, with the purpose of mitigating the effect caused by waste generated by food industries. Likewise, we seek to contribute to the environment by reducing the use of conventional plastics, which generate great pollution to the atmosphere, waters and soils. For the formulation of the biofilms, a factorial experimental design was used where the pH and pectin extraction time were varied with a 3×2 design; where the controllable factor of the process is the pH and the extraction time, with a response variable of the performance of the extraction process by the acid hydrolysis method. From the results obtained in the extraction of pectins, the biofilms were prepared and those with the best performance were selected.